The importance of personality towards employees' performance / Farah Affuza Khairudin - Khairudin, Farah Affuza (2014)
Personality is about out different ways of being human. Each person has different personality. This might due to several factors such as different background. Sometimes, problem may occur because of this different personality will influence the styles of thinking, feeling, and acting of the person. This includes the personality of employees in facing some situation in working environment. Indirectly, personality may effects employees' performance. Thus, the aim of this study is to describe the five dimensions of personality towards employees' performance among staff in some offices and department at Universiti Teknologi Malaysia, UTM.